2011
DOI: 10.1111/j.1365-2966.2011.18560.x
|View full text |Cite
|
Sign up to set email alerts
|

The ATLAS3D project - II. Morphologies, kinemetric features and alignment between photometric and kinematic axes of early-type galaxies

Abstract: We use the ATLAS 3D sample of 260 early-type galaxies to study the apparent kinematic misalignment angle, , defined as the angle between the photometric and kinematic major axes. We find that 71 per cent of nearby early-type galaxies are strictly aligned systems ( ≤ 5 • ), an additional 14 per cent have 5 • < ≤ 10 • and 90 per cent of galaxies have ≤ 15 • . Taking into account measurement uncertainties, 90 per cent of galaxies can be considered aligned to better than 5 • , suggesting that only a small fraction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
671
4
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 471 publications
(743 citation statements)
references
References 97 publications
66
671
4
2
Order By: Relevance
“…Or the two vectors may not align because we are observing the systems in projection (the orientation of a triaxial galaxy towards an observer is random). Interestingly, analysis presented by Franx et al (1991) showed that majority of early-type galaxies indeed had small misalignments (See also, Krajnović et al 2011). The most modern estimates on elliptical galaxy spin axes claim that a majority of elliptical galaxies appear like spiral galaxies with the gas and dust removed (Cappellari et al 2011), namely with spin vectors aligned with their short axes.…”
Section: Observational Samples and Galaxy Spin Vectorsmentioning
confidence: 99%
“…Or the two vectors may not align because we are observing the systems in projection (the orientation of a triaxial galaxy towards an observer is random). Interestingly, analysis presented by Franx et al (1991) showed that majority of early-type galaxies indeed had small misalignments (See also, Krajnović et al 2011). The most modern estimates on elliptical galaxy spin axes claim that a majority of elliptical galaxies appear like spiral galaxies with the gas and dust removed (Cappellari et al 2011), namely with spin vectors aligned with their short axes.…”
Section: Observational Samples and Galaxy Spin Vectorsmentioning
confidence: 99%
“…Integral field kinematic data from the ATLAS 3D are available for NGC 4371 and NGC 3945 (Krajnović et al 2011). Fig.…”
Section: Kinematic Comparisonsmentioning
confidence: 99%
“…One extreme example is the kinematically decoupled core found in some massive, early-type galaxies (e.g., Krajnović et al 2011) and in a few low-mass, early-type galaxies (e.g., Thomas et al 2006;Chilingarian et al 2007;Toloba et al 2014b, Gérou et al, 2015. These could be remnants of galaxy mergers or gas accretion, and are thus good indicators of the formation history of the galaxy.…”
Section: Introductionmentioning
confidence: 99%